Vomiting Infant - Adrianna Nicole Levesque; John R. Hughes; Robert Barnwell (Association of American Medical Colleges, 2012)
Abstract This case was created from a patient that was seen in the Emergency Department, and allows medical students and/or residents to recognize and diagnose pyloric stenosis. As such the resource contains a simulation case where child is projectile vomiting after meals and has been less interactive in the past 2 days, according to the parents. Initial vitals indicate tachycardia, hypotension, and the fact that the child is underweight. Intravenous access is difficult so the learner is expected to obtain intraosseous access. When fluids are given, vital signs improve. The child vomits during simulation and aspirates with resulting hypoxia until the airway is suctioned. A chemistry panel reveals hypochloremic metabolic alkalosis. The results of an ordered and performed ultrasound indicate pyloric stenosis. Pyloric stenosis is then diagnosed and a surgery consult is sought. This case has been used once in December 2011 at the San Antonio Military Medical Center's Simulation Center. Two staff members, six emergency medicine residents (3 EM1, 1 EM2, 2 EM3s), two internal medicine residents, and two medical students experienced this case. One member of the simulation center staff was also present. The case was successfully employed within 30 minutes and no changes were made to the case materials at that time. The case is designed to be reemployed yearly for residents and medical students.